Metodologías activas de aprendizaje y su incidencia en el rendimiento académico en los estudiantes de 7° de EGB de la UE Emigdio Esparza Moreno, Babahoyo. 2022 - Adrián Acosta, Shirley Dayanna (2022)
Active methodologies are teaching strategies; in which the student plays a very important role, where from scenarios and activities designed by the teacher, students build their knowledge. These work as an instrument of value because they are used for the development of the most used students in studying the elements of each related method with its foundation, its applied utility and the procedures used to produce results. The objective of this work is to determine the way in which active learning methodologies affect academic performance in 7th grade EGB students from the EU Emigdio Esparza Moreno, Babahoyo. Period 2022. Through the observation and the survey carried out, it was possible to verify the result of the proposed hypothesis and the answers were as expected, the students presented low academic disinterest causing low results in their performance, because the teachers do not apply the active learning methodologies necessary, this could be evidenced through the questionnaires, when carrying out the respective statistical analyzes they yielded the following: Teachers use traditional methods that do not contribute to the maximum development of the intellectual potential of the students, for this reason a severe didactic guide was applied in the active learning methodologies, for 7th EGB students from the EU Emigdio Esparza Moreno.